Exposure to Wood Smoke and Associated Health Effects in Sub-Saharan Africa: A Systematic Review - Onyinyechi Bede-Ojimadu; Orish Ebere Orisakwe (Ubiquity Press, 2020)
Background: Observational studies suggest that exposure to wood smoke is associated with a variety of adverse health effects in humans. Objective: We aimed to summarise evidence from sub-Saharan Africa on levels of exposure to pollutants in wood smoke and the association between such exposures and adverse health outcomes. Methods: PubMed and Google scholar databases were searched for original articles reporting personal exposure levels to pollutants or health outcomes associated with wood smoke exposure in Sub-Saharan African population. Results: Mean personal PM2.5 and carbon monoxide levels in the studies ranged from 26.3 ± 1.48 μg/m3 to 1574 ± 287μg/m3 and from 0.64 ± 2.12 ppm to 22 ± 2.4 ppm, respectively. All the reported personal PM2.5 exposure levels were higher than the World Health Organization's Air Quality Guideline (AQG) for 24-hour mean exposure. Use of wood fuels in domestic cooking is the major source of wood smoke exposure in this population. Occupational exposure to wood smoke included the use of wood fuels in bakery, fish drying, cassava processing and charcoal production. Females were exposed to higher levels of these pollutants than males of the same age range. Major determinants for higher exposure to wood smoke in SSA included use of unprocessed firewood, female gender and occupational exposure. We recorded strong and consistent associations between exposure to wood smoke and respiratory diseases including acute respiratory illness and impaired lung function. Positive associations were reported for increased blood pressure, low birth weight, oesophageal cancer, sick building syndrome, non-syndromic cleft lip and/or cleft palate and under-five mortality. Conclusion: There is high level of exposure to wood smoke in SSA and this exposure is associated with a number of adverse health effects. There is urgent need for aggressive programs to reduce wood smoke exposure in this population.